An equivalent norm of Herz spaces and its application to the Carleson operator - Sawano, Yoshihiro (Hilbert Journal of Mathematical Analysis, 2024)
By establishing a new norm equivalence on Herz spaces using the Muckenhoupt class, the boundedness of the maximal modulated singular integral operators is established. This boundedness also boils down to the boundedness of the Carleson operator over the real line.